The influence of digital marketing and MSMEs tax incentives on MSMEs sustainability - Naftaly, Rachel Kezia; Sitompul, Grace Orlyn; Simbolon, Richard Friendly (Jurnal Mantik, 2024)
This study aims to analyze the effect of digital marketing and MSMEs tax incentives on MSMES sustainability. The type of research used is quantitative. The population in this study were MSMEs, the number of respondents in this study were 104 MSMsEs. The data collection method used a questionnaire. This data is processed using spss. Based on the results of multiple linear regression obtained form regression equation Y = 32.490 + 0.364 + 0.646. The results of the research and partial hypothesis testing show that digital marketing has a significant effect on the MSMEs sustainability, MSMEs tax incentives have a significant effect on the MSMEs sustainability. Simultaneously digital marketing and MSME tax incentives  have a significant effect on the sustainability of MSMEs